Examining Factors Responsible For the Continued Illegal Use of Wildlife Resources at Bwindi Impenetrable Forest National Park. - Muhumuza, Ambrose (Kabale University, 2023)
The illegal use of wildlife is a threat to biodiversity globally, causing negative biological. ecological, economic, and social impacts and acting as a primary threat to maintaining national parks. At Bwindi impenetrable forest national park south western Uganda, When the national park was set up by an act of parliament in of Uganda 1991, it caused high levels of conflict and resistance from local people who became excluded from the area and its resources. As a result, in the years that followed, some 'integrated conservation and development' (ICD) interventions were carried out to reduce conflict by improving the livelihoods of communities living around Bwindi National Park. The study examined the factors responsible for the continued illegal use of wildlife resources at Bwindi Impenetrable Forest National Park.